2021
DOI: 10.1016/j.jiac.2020.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Optimal trough concentration of voriconazole with therapeutic drug monitoring in children: A systematic review and meta-analysis

Abstract: Objectives: This systematic review and meta-analysis was designed to determine the optimal trough concentration of voriconazole for children with invasive fungal infections (IFIs). Methods: We searched electronic databases (PubMed, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov and Japana Centra Revuo Medicina) for clinical studies describing the voriconazole trough concentration. We used stepwise cut-off values of 1.0e2.0 mg/L for efficacy and 3.0e6.0 mg/L for safety. The efficacy outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
(44 reference statements)
1
17
1
1
Order By: Relevance
“…In this study, 211 children with hematologic disorders, solid organ transplantation, and from Asian and non-Asian countries were included. The authors found that the efficacy of IFIs treatment increases significantly with cutoff values of ≥1.0 mg/L [27].…”
Section: Timing Of Initial Tdm and Target Concentration Of Vczmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, 211 children with hematologic disorders, solid organ transplantation, and from Asian and non-Asian countries were included. The authors found that the efficacy of IFIs treatment increases significantly with cutoff values of ≥1.0 mg/L [27].…”
Section: Timing Of Initial Tdm and Target Concentration Of Vczmentioning
confidence: 98%
“…High plasma concentration of VCZ might be associated with an increased risk of toxicity. As VCZ is well tolerated in children with a lower rate of adverse effects (AEs), toxicity targets have not been validated for this population so far [27]. However, several studies have reported the incidence of adverse drug reactions.…”
Section: Timing Of Initial Tdm and Target Concentration Of Vczmentioning
confidence: 99%
“…However, data on the target range of voriconazole concentrations in children are lacking because most studies are limited by small sample sizes and other factors. Hanai et al [ 74 ] used a similar approach to suggest that the target concentration range for voriconazole in children, particularly for Asian populations, is 1.0–3.0 μg/mL.…”
Section: Antifungal Stewardshipmentioning
confidence: 99%
“…Approved in 2002 by the FDA, voriconazole is a broad-spectrum triazole antifungal agent that has become a mainstay of both primary and salvage treatment for invasive aspergillosis and candidiasis [1,[7][8][9][10][11][12][13][14]. Several publications, mainly in adults but also in children, suggest that therapeutic drug monitoring (TDM) improves the efficacy and safety of voriconazole [1,8,[15][16][17][18][19][20][21][22][23][24]. As between-subject differences in voriconazole plasma concentrations (PC) are more marked in children than in adults [25][26][27][28][29][30], monitoring of trough concentrations is particularly important in children to ensure optimal treatment.…”
Section: Introductionmentioning
confidence: 99%